Assessment of the Cause of Variation and Extension of Time in Water Supply Projects (OODBODHAN, 2026)
Public water supply projects in Nepal frequently face cost overruns and schedule delays. It mostly investigates the causes and extent of Variation Orders (VO) and Extensions of Time (EOT) in water supply projects implemented under the Department of Water Supply and Sewerage Management (DWSSM) in Gandaki Province, Nepal. Primary data were collected through questionnaires from clients, contractors, and water user committees, while secondary data were obtained from EOT and VO approval reports. Relative Importance Index (RII) and Severity Index (SI) were used to rank and prioritize the causes of VO and EOT. Among 25 identified causes, inadequate coordination among stakeholders with RII 0.785 and communication delay from the project manager with SI 78.889 were found to be the most significant causes of EOT. It reflected different ranking orders using different tools. Similarly, among 13 identified causes of VO, mistakes in the bill of quantities with RII 0.852 and incomplete design with SI 85.185 were the most influential causes of VO. Spearman’s rho correlation analysis showed a strong positive correlation between the causes of VO and EOT, with a correlation coefficient of 0.805 and a significance value of p = 0.000 (